Woven textiles a designer's guide - Kearley, Sharon (The Crowood Press, 2014)
"Weaving is an age-old craft but it has boundless potential. The beauty and joy of weaving a finished piece of cloth can be enhanced by creating your own designs and using the latest ideas and techniques. This book explains to the novice how to start weaving textiles, but also develops techniques for the more experienced so they can learn to appreciate colour, patterns and structures, and thereby design their own richly-textured cloth. As well as practical information on how to get started, Woven Textiles looks at design concepts and how to experiment with ideas, such as mark-making skills on paper and embroidery on fabric. It introduces new weave structures and suggests ways to explore colours and yarns"--Provided by publisher.